Level Of Well-being At Work Among University Academics Field Study On A Sample Of Professors In The Department Of Psychology At The University Of M’sila - nekbil, boudjema (El Omda in Linguistics and Discourse Analysis, 2024)
The study aimed to reveal the level of sense of well-being at work among professors working in the Department of Psychology at the University of M'sila. The descriptive approach was relied upon. The researcher used a ready-made tool to measure the level of sense of well-being at work, which contains (16) statements. A sample of professors of the Department of Science was chosen. Psychology was estimated at (31) professors, and the study reached the following results: - Professors working in the Department of Psychology at the University of M'sila feel a low level of well-being at work in their workplace.